A Recipe for Globalization: Sociology of a Trade Fair Organizer - (:unkn) unknown (My University, 2016)
In this paper we study the globalization process through the observation of ‘market professionals’ whose business is to organize international marketplaces. We focus on the case of a trade fair for the distribution of TV programmes in sub-Saharan Africa. Until the 2000s, African TV channels had several ways to acquire programmes for free. This industry slowly became a market after political and infrastructural changes. This trade fair follows this process and is the first event to bring together international TV programme distributors and African TV channels. We describe the activities of the trade fair organizer, which can be described as the ingredients in a recipe for globalization. Beyond the use of devices to organize the market, the core of his business lies in what we call cultural agency. The goal is to bring the practices of local and international actors into alignment. But this is an example of what economists call a two-sided market and the organizer considers buyers of the trade-fair as products to be sold to sellers. As a result, this process of cultural agency is asymmetrical and requires African buyers to adapt their practices to international sellers. We thus show in this paper that market globalization entails social costs for the poorer players.
Keywords: African Research